A geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst, a preparation method and application thereof

CN122558501BActive Publication Date: 2026-10-16LANZHOU UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611071040.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-16
Estimated Expiration
2046-07-20

AI Technical Summary

Technical Problem

[0002]光热催化技术在二氧化碳减排与资源化利用中潜力巨大,但现有催化剂面临三大瓶颈:一是载体性能差,化学法成本高,而直接利用工业固废因杂质多导致强度低、孔隙发育不全,吸附弱且易粉化难回收;二是活性组分易流失,钴基等金属氧化物与载体仅靠物理吸附,缺乏化学键合,在反应气流冲刷及长期热应力下极易脱落失活;三是光热效率低,单一金属氧化物光吸收窄、载流子复合率高,对可见及近红外光利用率极低

Benefits of technology

本发明通过地聚物载体、氧化钴与银单质的协同作用:采用重液分离提取低密度漂珠,结合水热活化造孔,大幅提升了固体废弃物粉煤灰的比表面积和吸附性能,结合二氧化碳养护,在吸收固定二氧化碳的同时显著增强了载体强度;采用硅烷偶联剂对多孔氧化钴进行表面改性,通过化学键合将氧化钴与地聚物牢固连接,有效防止活性组分脱落流失,并引入银纳米颗粒,大幅增强了催化剂对可见及近红外光的吸收,既提升了光热转换效率,又促进内部电荷快速分离,提高了光热催化活性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122558501B_ABST
    Figure CN122558501B_ABST
Patent Text Reader

Abstract

The present application relates to the technical field of catalyst preparation, and particularly discloses a geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst, a preparation method and application thereof, the preparation method comprising the following steps: obtaining modified mineralized geopolymer by CO2 curing of modified floating bead powder and alkali activator; then, obtaining composite slurry by composite reaction of the modified mineralized geopolymer and porous cobalt oxide modified by a silane coupling agent; then, obtaining an intermediate catalyst by drying and heat treatment; finally, obtaining the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst by silver salt reduction doping, washing and drying. The silane coupling agent is chemically bonded to prevent the loss of active components, CO2 curing enhances the strength of the carrier, and the introduction of silver nanoparticles broadens the spectral absorption, greatly improves the photo-thermal conversion efficiency and catalytic activity, so that the catalyst has excellent structural stability and easy separation and recovery characteristics, and can be widely applied to the fields of practical environmental protection and new energy, such as the preparation of high-value-added chemicals by photo-thermal catalytic CO2 hydrogenation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalyst preparation technology, specifically to a geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst, its preparation method, and its application. Background Technology

[0002] Photothermal catalysis technology has great potential in carbon dioxide emission reduction and resource utilization, but existing catalysts face three major bottlenecks: First, the support performance is poor, the chemical method is costly, and the direct use of industrial solid waste results in low strength and incomplete pore development due to many impurities, weak adsorption, easy pulverization and difficulty in recycling; Second, the active components are easily lost, and cobalt-based and other metal oxides rely only on physical adsorption with the support, lacking chemical bonding, and are easily deactivated under the scouring of the reaction gas flow and long-term thermal stress; Third, the photothermal efficiency is low, the light absorption of single metal oxides is narrow and the carrier recombination rate is high, resulting in extremely low utilization of visible and near-infrared light.

[0003] Therefore, there is an urgent need in this field to develop a novel composite photothermal catalyst that possesses excellent mechanical strength and easy separation and recovery characteristics, ensures that the catalytic components are firmly bound to prevent loss, and broadens the spectral absorption range to improve photothermal conversion efficiency. This would improve the problems of existing catalysts, such as difficulty in recovery, easy instability, and low efficiency, and enhance the overall performance and operational stability of adsorption-photothermal catalysis. Summary of the Invention

[0004] The purpose of this invention is to provide a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, its preparation method, and its application, to solve the problems mentioned in the background art. To achieve the above objective, this invention provides the following technical solution: A method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst includes the following steps: S1. Preparation of modified mineralized geopolymer: By mass, 12-16 parts of modified cenosphere powder and 5-12 parts of alkaline activator solution are mixed and stirred, and cured in a CO2 atmosphere at 50-70℃ for 24-48 hours. After demolding, the mixture is crushed and ground through a 200-300 mesh sieve to obtain the modified mineralized geopolymer. S2. Composite and cross-linking reaction: Mix 14-18 parts of modified mineralized geopolymer with 80-150 parts of deionized water to form a uniform slurry, add 1.5-4 parts of silane coupling agent to modify porous cobalt oxide, ultrasonically disperse for 10-20 min, and then mechanically stir at 40-60℃ for 2-4 h to obtain geopolymer / porous cobalt oxide composite slurry; S3. Drying and heat treatment: Dry the geopolymer / porous cobalt oxide composite slurry at 40-80℃ for 24-48h, wash it with water 3-5 times, dry it again at 40-80℃ for 24-48h, and then heat treat it in air at 350-450℃ for 20-40min to obtain the intermediate catalyst. S4, Silver doping: Add 15-20 parts of intermediate catalyst and 0.15-0.4 parts of soluble silver salt to 150-300 parts of deionized water. After ultrasonic dispersion, add 30-100 parts of sodium borohydride alkaline solution dropwise and stir for 0.5-1 hour. Wash with distilled water and anhydrous ethanol alternately 3-5 times, dry in a vacuum drying oven at 50-70℃ for 3-5 hours, and then pass through a 300-500 mesh sieve to obtain a geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0005] Preferably, the preparation of modified celery micropowder in step S1 includes the following steps: S11. Weigh 180-500 parts of anhydrous zinc chloride solid by mass, and slowly add it to 120-300 parts of deionized water under stirring and heating at 60-80℃. After the solid is completely dissolved and cooled to room temperature, adjust the solution density to 1.65-1.75 g / cm³ to obtain the initial heavy liquid. S12. Mix 100-200 parts of fly ash with the initial heavy liquid at a liquid-solid mass ratio of 3:1-5:1, stir and disperse at 60-80℃, then separate by hydrocyclone separator or static sedimentation, and collect the floating low-density cenosphere phase. S13. Mix the floating low-density cenosphere phase with 300-800 parts of deionized water, and perform hydrothermal activation treatment at 120-130℃ for 2-3 hours. After the reaction is completed, allow it to cool naturally, perform solid-liquid separation to collect the solid, and wash it with deionized water by centrifugation 3-4 times. Then dry it at 105-110℃, grind it through a 200-300 mesh sieve to obtain modified cenosphere micro powder.

[0006] Preferably, the preparation of silane coupling agent modified porous cobalt oxide in step S2 includes the following steps: S21. By mass, add 15-30 parts of porous cobalt oxide to 150-300 parts of ethanol-water mixed solution, adjust the pH to 3-4 with glacial acetic acid, add 0.15-1.5 parts of silane coupling agent KH-560, ultrasonically disperse at 40-60℃ for 2-4 hours, and then stir and reflux at 60-80℃ for 4-6 hours. S22. After the reaction is complete, the solid is collected by centrifugation, washed 3-5 times with anhydrous ethanol, vacuum dried at 80-100℃ for 10-14h, and ground through an 800-1200 mesh sieve to obtain silane coupling agent modified porous cobalt oxide.

[0007] Preferably, the preparation of porous cobalt oxide in step S21 includes the following steps: S211. By weight, dissolve 80-120 parts of water-soluble cobalt salt in 400-1000 parts of deionized water, add 40-100 parts of precipitant, and stir at 60-80℃ until completely dissolved. S212 is then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 120-160℃ for 12-24 hours to generate a porous cobalt hydroxide precursor. S213. After the reaction is complete, centrifuge and wash until neutral, dry at 80-100℃, then calcine in air at 300-400℃ for 2-3 hours, grind through an 800-1200 mesh sieve to obtain porous cobalt oxide.

[0008] Preferably, the alkaline activator is prepared by mixing sodium hydroxide, anhydrous sodium metasilicate and water in a mass ratio of 1:(2-4):(5-10) and then allowing it to stand and age for 12-24 hours. Preferably, the soluble silver salt is one or more of silver nitrate, silver acetate, silver perchlorate, or silver trifluoromethanesulfonate.

[0009] Preferably, the mass fraction of ethanol in the ethanol-water mixed solution is 90%-95%.

[0010] Preferably, the water-soluble cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, or cobalt sulfate; Preferably, the precipitant is one or more of urea, hexamethylenetetramine, or ammonium carbonate.

[0011] Preferably, the concentration of the sodium borohydride alkaline solution is 0.1-0.5 mol / L.

[0012] A geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst was prepared by the above method.

[0013] Application of the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst prepared according to the above preparation method in photothermal catalytic carbon dioxide hydrogenation reaction.

[0014] Compared with the prior art, the beneficial effects of the present invention are: This invention utilizes the synergistic effect of geopolymer carrier, cobalt oxide, and elemental silver: Low-density cenospheres are extracted using heavy liquid separation, combined with hydrothermal activation to create pores, significantly increasing the specific surface area and adsorption performance of fly ash, a solid waste material. Combined with carbon dioxide curing, the carrier strength is significantly enhanced while absorbing and fixing carbon dioxide. Silane coupling agents are used to modify the surface of porous cobalt oxide, chemically bonding it firmly to the geopolymer, effectively preventing the loss of active components. Furthermore, the introduction of silver nanoparticles significantly enhances the catalyst's absorption of visible and near-infrared light, improving photothermal conversion efficiency and promoting rapid internal charge separation, thereby increasing photothermal catalytic activity. Attached Figure Description

[0015] Figure 1 This is a process flow diagram for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst according to the present invention; Figure 2 The XRD patterns of the catalysts prepared in Examples 1, 3 and Comparative Example 1 of this invention are shown below. Figure 3 The PL spectra of the catalysts prepared in Examples 1, 3 and Comparative Example 1 of this invention are shown below. Figure 4 The graph shows the performance test results of the catalyst prepared in Comparative Example 1 of this invention under a hydrogen to carbon dioxide ratio of 5:1. Figure 5 The graph shows the performance test results of the catalyst prepared in Example 3 of the present invention under a hydrogen to carbon dioxide ratio of 5:1. Figure 6 The graph shows the performance test results of the catalyst prepared in Example 3 of this invention under a hydrogen to carbon dioxide ratio of 4.5:1. Figure 7 The graph shows the performance test results of the catalyst prepared in Example 3 of this invention under a hydrogen to carbon dioxide ratio of 4:1. Detailed Implementation

[0016] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0017] Please see Figures 1-7 The present invention provides a technical solution: Example 1 In this embodiment, the preparation of precursor materials is required before preparing the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0018] I. Preparation of Pre-processing Materials 1. Preparation of sodium borohydride alkaline solution First, prepare 30g of a 0.05mol / L sodium hydroxide aqueous solution (by weighing 0.06g of sodium hydroxide solid and dissolving it in 30g of deionized water). Then, weigh 0.114g of sodium borohydride solid and completely dissolve it in the 30g sodium hydroxide aqueous solution to obtain a 0.1mol / L sodium borohydride alkaline solution.

[0019] 2. Preparation of ethanol-water mixed solution Measure 135.0g of anhydrous ethanol and 15.0g of deionized water, mix well, and set aside.

[0020] 3. Preparation of alkaline activators Mix 1g of sodium hydroxide, 2g of anhydrous sodium metasilicate and 5g of deionized water, and let stand for 24 hours.

[0021] 4. Preparation of porous cobalt oxide S211. Dissolve 80g of cobalt nitrate hexahydrate in 400g of deionized water, add 40g of urea, and stir at 60℃ until completely dissolved. S212 was then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 120°C for 12 hours to generate a porous cobalt hydroxide precursor. S213. After the reaction is complete, centrifuge and wash until neutral, dry at 80°C, then calcine in air at 300°C for 2 hours, grind through an 800-mesh sieve to obtain porous cobalt oxide.

[0022] 5. Preparation of porous cobalt oxide modified with silane coupling agent S21. Add 15g of porous cobalt oxide to 150g of ethanol-water mixed solution, adjust the pH to 3 with glacial acetic acid, add 0.15g of silane coupling agent KH-560, ultrasonically disperse at 40℃ for 2h, and then stir and reflux at 60℃ for 4h. S22. After the reaction is complete, the solid is collected by centrifugation, washed three times with anhydrous ethanol, dried under vacuum at 80°C for 10 hours, and ground through an 800-mesh sieve to obtain silane coupling agent modified porous cobalt oxide.

[0023] 6. Preparation of modified celery micropowder S11. Weigh 180g of anhydrous zinc chloride solid, and slowly add it to 120g of deionized water under stirring and heating at 60℃. After the solid is completely dissolved and cooled to room temperature, adjust the solution density to 1.65g / cm³ to obtain the initial heavy liquid. S12. Mix 100g of fly ash with 300g of initial heavy liquid at a liquid-solid mass ratio of 3:1, stir and disperse at 60℃, then separate by hydrocyclone separator or static sedimentation, and collect the floating low-density cenosphere phase. S13. The floating low-density cenosphere phase is mixed with 300g of deionized water and hydrothermally activated at 120℃ for 2h. After the reaction is completed, the mixture is naturally cooled, and the solid is collected by solid-liquid separation. The solid is then washed three times by centrifugation with deionized water, dried at 105℃, and ground through a 200-mesh sieve to obtain modified cenosphere micro powder.

[0024] II. A method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, comprising the following steps: S1. Preparation of modified mineralized geopolymer: Mix 12g of modified celery micro powder with 5g of alkali activator solution, stir, and cure in a CO2 atmosphere at 50℃ for 24h. After demolding, crush and grind through a 200-mesh sieve to obtain modified mineralized geopolymer. S2. Composite and cross-linking reaction: 14g of modified mineralized geopolymer and 80g of deionized water were mixed and dispersed into a uniform slurry. 1.5g of silane coupling agent was added to modify porous cobalt oxide. The mixture was ultrasonically dispersed for 10min and then mechanically stirred at 40℃ for 2h to obtain geopolymer / porous cobalt oxide composite slurry. S3. Drying and heat treatment: The geopolymer / porous cobalt oxide composite slurry was dried at 40℃ for 24h, washed with water 3 times, dried at 40℃ for 24h again, and then heat-treated in air at 350℃ for 20min to obtain the intermediate catalyst. S4, Silver doping: 15g of intermediate catalyst and 0.15g of silver nitrate were added to 150g of deionized water and dispersed by ultrasonication. Then, 30g of sodium borohydride alkaline solution was added dropwise and stirred for 0.5h. The mixture was washed three times alternately with distilled water and anhydrous ethanol, dried in a vacuum drying oven at 50℃ for 3h, and then passed through a 300-mesh sieve to obtain the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0025] Example 2 In this embodiment, the preparation of precursor materials is required before preparing the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0026] I. Preparation of Pre-processing Materials 1. Preparation of sodium borohydride alkaline solution First, prepare 100g of a 0.1mol / L sodium hydroxide aqueous solution (by weighing 0.4g of sodium hydroxide solid and dissolving it in 100g of deionized water). Then, weigh 1.9g of sodium borohydride solid and completely dissolve it in the 100g sodium hydroxide aqueous solution to obtain a 0.5mol / L sodium borohydride alkaline solution.

[0027] 2. Preparation of ethanol-water mixed solution Measure 285g of anhydrous ethanol and 15.0g of deionized water, mix well, and set aside.

[0028] 3. Preparation of alkaline activators Mix 1g of sodium hydroxide, 4g of anhydrous sodium metasilicate and 10g of deionized water, and let stand for 24 hours.

[0029] 4. Preparation of porous cobalt oxide S211. Dissolve 120g of cobalt nitrate hexahydrate in 1000g of deionized water, add 100g of urea, and stir at 80℃ until completely dissolved. S212 was then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 160°C for 24 hours to generate a porous cobalt hydroxide precursor. S213. After the reaction is complete, centrifuge and wash until neutral, dry at 100℃, then calcine in air at 400℃ for 3 hours, grind through a 1200-mesh sieve to obtain porous cobalt oxide.

[0030] 5. Preparation of porous cobalt oxide modified with silane coupling agent S21. Add 30g of porous cobalt oxide to 300g of ethanol-water mixed solution, adjust the pH to 4 with glacial acetic acid, add 1.5g of silane coupling agent KH-560, ultrasonically disperse at 60℃ for 4h, and then stir and reflux at 80℃ for 6h. S22. After the reaction is complete, the solid is collected by centrifugation, washed 5 times with anhydrous ethanol, dried under vacuum at 100°C for 14 hours, and ground through a 1200-mesh sieve to obtain silane coupling agent modified porous cobalt oxide.

[0031] 6. Preparation of modified celery micropowder S11. Weigh 500g of anhydrous zinc chloride solid, and slowly add it to 300g of deionized water while stirring and heating at 80℃. After the solid is completely dissolved and cooled to room temperature, adjust the solution density to 1.75g / cm³ to obtain the initial heavy liquid. S12. Mix 200g of fly ash with 1000g of initial heavy liquid at a liquid-solid mass ratio of 5:1, stir and disperse at 80℃, then separate by hydrocyclone separator or static sedimentation, and collect the floating low-density cenosphere phase. S13. The floating low-density cenosphere phase is mixed with 800g of deionized water and hydrothermally activated at 130℃ for 3h. After the reaction is completed, the mixture is naturally cooled, and the solid is collected by solid-liquid separation. The solid is then washed 4 times by centrifugation with deionized water, dried at 110℃, and ground through a 300-mesh sieve to obtain modified cenosphere micro powder.

[0032] II. A method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, comprising the following steps: S1. Preparation of modified mineralized geopolymer: 16g of modified celery micro powder and 12g of alkali activator solution were mixed and stirred, and cured at 70℃ in CO2 atmosphere for 48h. After demolding, the mixture was crushed and ground through a 300-mesh sieve to obtain the modified mineralized geopolymer. S2. Composite and cross-linking reaction: 18g of modified mineralized geopolymer and 150g of deionized water were mixed and dispersed into a uniform slurry. 4g of silane coupling agent was added to modify porous cobalt oxide. The mixture was ultrasonically dispersed for 20min and then mechanically stirred at 60℃ for 4h to obtain geopolymer / porous cobalt oxide composite slurry. S3. Drying and heat treatment: The geopolymer / porous cobalt oxide composite slurry was dried at 80℃ for 48h, washed with water 5 times, dried at 80℃ for 48h again, and then heat-treated in air at 450℃ for 40min to obtain the intermediate catalyst. S4, Silver doping: 20g of intermediate catalyst and 0.4g of silver nitrate were added to 300g of deionized water and dispersed by ultrasonication. Then, 100g of sodium borohydride alkaline solution was added dropwise and stirred for 1h. The mixture was washed 5 times alternately with distilled water and anhydrous ethanol, dried in a vacuum drying oven at 70℃ for 5h, and then passed through a 500-mesh sieve to obtain the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0033] Example 3 In this embodiment, the preparation of precursor materials is required before preparing the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0034] I. Preparation of Pre-processing Materials 1. Preparation of sodium borohydride alkaline solution First, prepare 100g of a 0.1mol / L sodium hydroxide aqueous solution (by weighing 0.4g of sodium hydroxide solid and dissolving it in 100g of deionized water). Then, weigh 1.135g of sodium borohydride solid and completely dissolve it in the 100g sodium hydroxide aqueous solution to obtain a 0.3mol / L sodium borohydride alkaline solution.

[0035] 2. Preparation of ethanol-water mixed solution Measure 185g of anhydrous ethanol and 15.0g of deionized water, mix them thoroughly, and set aside.

[0036] 3. Preparation of alkaline activators Mix 1g of sodium hydroxide, 3g of anhydrous sodium metasilicate and 8g of deionized water, and let stand for 24 hours.

[0037] 4. Preparation of porous cobalt oxide S211. Dissolve 100g of cobalt nitrate hexahydrate in 700g of deionized water, add 70g of urea, and stir at 70℃ until completely dissolved. S212 was then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 140°C for 18 hours to generate a porous cobalt hydroxide precursor. S213. After the reaction is complete, centrifuge and wash until neutral, dry at 90°C, then calcine in air at 350°C for 2.5 hours, grind through a 1000-mesh sieve to obtain porous cobalt oxide.

[0038] 5. Preparation of porous cobalt oxide modified with silane coupling agent S21. Add 20g of porous cobalt oxide to 200g of ethanol-water mixed solution, adjust the pH to 3.5 with glacial acetic acid, add 0.8g of silane coupling agent KH-560, ultrasonically disperse at 50℃ for 3h, and then stir and reflux at 70℃ for 5h. S22. After the reaction is complete, the solid is collected by centrifugation, washed 4 times with anhydrous ethanol, dried under vacuum at 90°C for 12 hours, and ground through a 1000-mesh sieve to obtain silane coupling agent modified porous cobalt oxide.

[0039] 6. Preparation of modified celery micropowder S11. Weigh 340g of anhydrous zinc chloride solid, and slowly add it to 210g of deionized water under stirring and heating at 70℃. After the solid is completely dissolved and cooled to room temperature, adjust the solution density to 1.70g / cm³ to obtain the initial heavy liquid. S12. Mix 150g of fly ash with 600g of initial heavy liquid at a liquid-solid mass ratio of 4:1, stir and disperse at 70℃, then separate by hydrocyclone separator or static sedimentation, and collect the floating low-density cenosphere phase. S13. The floating low-density cenosphere phase was mixed with 550g of deionized water and hydrothermally activated at 125℃ for 2.5h. After the reaction was completed, the mixture was naturally cooled, and the solid was collected by solid-liquid separation. The solid was then washed three times by centrifugation with deionized water, dried at 110℃, and ground through a 250-mesh sieve to obtain modified cenosphere micro powder.

[0040] II. A method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, comprising the following steps: S1. Preparation of modified mineralized geopolymer: 14g of modified celery micro powder and 8g of alkali activator solution were mixed and stirred, and cured at 60℃ in CO2 atmosphere for 36h. After demolding, the mixture was crushed and ground through a 250-mesh sieve to obtain the modified mineralized geopolymer. S2. Composite and cross-linking reaction: 16g of modified mineralized geopolymer and 120g of deionized water were mixed and dispersed into a uniform slurry. 2.75g of silane coupling agent was added to modify porous cobalt oxide. The mixture was ultrasonically dispersed for 15min and then mechanically stirred at 50℃ for 3h to obtain geopolymer / porous cobalt oxide composite slurry. S3. Drying and heat treatment: The geopolymer / porous cobalt oxide composite slurry was dried at 60℃ for 36h, washed with water 4 times, dried at 60℃ for 36h again, and then heat-treated in air at 400℃ for 30min to obtain the intermediate catalyst. S4, Silver doping: 18g of intermediate catalyst and 0.25g of silver nitrate were added to 200g of deionized water and dispersed by ultrasonication. Then, 65g of sodium borohydride alkaline solution was added dropwise and stirred for 45min. The mixture was washed 4 times alternately with distilled water and anhydrous ethanol, dried in a vacuum drying oven at 60℃ for 4h, and then passed through a 400-mesh sieve to obtain the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst.

[0041] Comparative Example 1 The only difference from Example 3 is that: in step S1, ordinary geopolymer is used instead of modified mineralized geopolymer; in step S2, ordinary porous cobalt oxide is used instead of silane coupling agent modified porous cobalt oxide; and the silver doping operation in step S4 is omitted. The remaining raw material ratios, process parameters and operation steps are consistent with those of Example 3.

[0042] Comparative Example 2 The only difference from Example 3 is that ordinary geopolymer is used instead of modified mineralized geopolymer in step S1, and the silver doping operation in step S4 is omitted. The remaining raw material ratios, process parameters and operation steps are consistent with those of Example 3.

[0043] Comparative Example 3 The only difference from Example 3 is that ordinary porous cobalt oxide is used instead of silane coupling agent to modify porous cobalt oxide in step S2, and the silver doping operation in step S4 is omitted. The remaining raw material ratios, process parameters and operation steps are consistent with those of Example 3.

[0044] Comparative Example 4 The only difference from Example 3 is that the silver doping operation in step S4 is omitted, while the remaining raw material ratios, process parameters and operating steps are the same as in Example 3.

[0045] I. Performance Testing The performance of the geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalysts prepared in Examples 1-3 and Comparative Examples 1-4 was tested: 1. Recycling rate and structural stability: Referring to GB / T 35110-2017 "Test Methods for Performance of Photocatalytic Materials in Nanotechnology", the catalyst was added to the reaction solution, and after the photocatalytic reaction was completed, it was centrifuged and recovered. After washing and drying, it was weighed. This process was repeated 5 times, and the final mass retention rate was calculated to evaluate the anti-pulverization and anti-leakage performance. 2. Specific surface area: Referring to GB / T 19587-2017 "Determination of specific surface area of ​​solid substances by gas adsorption BET method", a fully automated specific surface area and porosity analyzer was used to conduct nitrogen adsorption-desorption experiments at liquid nitrogen temperature. The specific surface area of ​​the sample was calculated by the BET equation to evaluate the pore development degree and adsorption enrichment capacity of the catalyst. 3. Photocurrent density: Using a three-electrode system and Na2SO4 electrolyte, the transient photocurrent density was measured by chronoamperometry under visible light irradiation to evaluate the photogenerated carrier separation efficiency and interfacial charge transport capability.

[0046] The performance test results are as follows: Table 1: Performance Test Results As shown in Table 1, combining the performance data of Comparative Examples 1-4 and Example 3, it can be seen that with the gradual introduction of different modification processes, the various properties of the catalysts show corresponding changing trends: Comparative Example 1 (unmodified) has relatively poor performance in all aspects; Comparative Example 2 only modifies porous cobalt oxide with silane coupling agent, and the photocurrent increases to 6.1 mA / cm², but because the geopolymer is not modified, the support strength is insufficient, resulting in poor mechanical stability of the catalyst, and the recycling rate is still only 81.3%; Comparative Example 3 only modifies mineralized geopolymer, and the recovery rate increases to 93.5% and the specific surface area increases to 192 m² / g, but because the cobalt oxide is not modified, the photocurrent is only 5.3 mA / cm², indicating that the interfacial transport resistance is large; Comparative Example 4 modifies both geopolymer and cobalt oxide (without silver), and the overall performance is further improved, but the lack of silver doping results in a certain gap in photocurrent density compared with Example 3 (12.4 mA / cm²), which reflects the role of silver nanoparticles in improving photothermal conversion efficiency and promoting carrier separation.

[0047] II. Material Characterization Material characterization was performed on some representative samples (Example 1, Example 3, and Comparative Example 1): 1. Crystal structure and phase analysis: Referring to GB / T 33862-2017 "X-ray diffraction analysis method for nanomaterials", X-ray diffractometer (XRD) was used to scan and test the catalyst, and the diffraction pattern was recorded to analyze the crystal structure, phase composition and carbonization enhancement mechanism of the material. 2. Photogenerated carrier recombination efficiency: The photoluminescence spectrum (PL) of the catalyst was measured at a specific excitation wavelength using a fluorescence spectrophotometer to evaluate the separation and recombination efficiency of photogenerated electron-hole pairs; The material characterization results are as follows: like Figure 2 The XRD pattern showed that the characteristic peaks of the sample were in high agreement with the standard cards for Co3O4 and Ag, confirming the successful loading of the active component and the integrity of the crystal structure. Based on this, PL spectroscopy was further performed to investigate the influence of this composite structure on carrier behavior. Figure 3 As shown, the fluorescence intensity of the silver-doped sample was significantly reduced, indicating that the recombination rate of photogenerated electron-hole pairs was significantly decreased.

[0048] III. Application Performance and Operating Condition Testing Catalytic application performance and operating conditions were tested on some representative samples (Example 1, Example 3 and Comparative Example 1): 1. CO2 hydrogenation catalytic performance: In a fixed-bed reactor, a xenon lamp (500 mW / cm²) was used as the light source, and the reaction was carried out under H2 / CO2 (volume ratio 4.5:1) conditions. The tail gas was analyzed by online gas chromatography to detect and calculate the carbon dioxide conversion rate, carbon monoxide (CO) yield, and methane (CH4) yield and selectivity, in order to evaluate the photothermal catalytic activity and the suppression of reverse water-gas shift (RWGS) side reactions. 2. Adaptability test to operating conditions: In a fixed-bed reactor, the volume ratio of H2 / CO2 mixture is changed, and the changes in CO2 conversion rate and product selectivity of the catalyst under fluctuating gas ratio are tested to evaluate the catalyst's anti-interference ability and adaptability to operating conditions.

[0049] The application performance and operating condition test results are as follows: Figure 4-5 The comparison shows that, under the same reaction conditions of hydrogen to carbon dioxide volume ratio of 5:1, the catalyst prepared in Example 3 of this invention, compared with Comparative Example 1, exhibits significantly improved CH4 selectivity and CH4 yield, while significantly reduced carbon monoxide (CO) yield. Figure 4 It can be seen that the CH4 selectivity of Comparative Example 1 (without modified mineralized geopolymer, silane coupling agent-modified porous cobalt oxide, and silver doping) at 300℃, 350℃, and 400℃ was 59.93%, 67.70%, and 79.64%, respectively, and the CH4 yields were 150.4, 289.6, and 551.7 mmol·gcat, respectively. -1 ·h -1 And accompanied by high CO yields, at 82.4, 138.1, and 141.0 mmol·gcat, respectively. -1 ·h -1 ; and by Figure 5 It can be seen that, in Example 3, the CH4 selectivity at 300℃, 350℃, and 400℃ was as high as 85.33%, 88.79%, and 87.28%, respectively, and the CH4 yields were 469.7, 446.6, and 553.5 mmol·gcat, respectively. -1 ·h -1 Furthermore, CO yields decreased to 80.7, 56.4, and 80.7 mmol·gcat, respectively. -1 ·h -1 The CH4 yield increased by more than three times at 300℃. This fully demonstrates that the present invention effectively regulates the reaction pathway and suppresses the side reaction of CO generation in reverse water-gas shift (RWGS) by modifying mineralized geopolymers to enhance the strength and adsorption of the carrier, using silane coupling agents to prevent the loss of active components through chemical bonding, and using silver nanoparticles to broaden spectral absorption and promote carrier separation. This effectively suppresses side reactions and achieves a significant leap in catalytic activity and CH4 selectivity.

[0050] Figure 5-7 The comparison shows that the catalyst prepared in Example 3 of this invention exhibits excellent catalytic performance and adaptability to different hydrogen / carbon dioxide volume ratios. Figure 5 The ratio was adjusted to 4.5:1. Figure 6 At 350℃ and 400℃, the CO2 conversion rate significantly increased from 21.75% (300℃), 44.97% (350℃), and 47.55% (400℃) to 63.03%, 64.54%, and 69.02%, respectively. The CH4 yield at 350℃ and 400℃ reached 774.9 mmol·gcat, respectively. -1 ·h -1 and 888.3 mmol·gcat -1 ·h -1 The CH4 selectivity was as high as 90.58% and 90.07%; when the H2 / CO2 volume ratio was further adjusted to 4:1 ( Figure 7 Although the CO2 conversion rate decreased (54.94% at 400℃), the CH4 yield remained at a high level (859.45 mmol·gcat at 400℃). -1 ·h -1 Furthermore, the CH4 selectivity remained consistently above 82.46%, although the CO yield showed a certain degree of recovery. These results indicate that the catalyst of this invention can effectively cope with fluctuations in the gas ratio. A hydrogen-rich environment is more conducive to the methanation reaction and inhibits CO formation. It maintains high CH4 selectivity, low CO yield, and good CO2 conversion capacity over a wide range of hydrogen-to-carbon ratios. Its overall performance is optimal, especially at an H2 / CO2 ratio of 4.5:1, demonstrating excellent anti-interference capabilities and practical application potential.

[0051] In summary, this invention strengthens the support substrate through "heavy liquid separation-hydrothermal activation-CO2 curing," utilizes silane coupling agents to achieve chemical bonding of active components, and introduces silver nanoparticles to excite a plasmonic resonance effect, successfully constructing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst with both high structural stability and high photothermal catalytic activity. This geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst not only effectively overcomes the technical bottlenecks of traditional catalysts, such as easy pulverization, easy component loss, and low photothermal conversion efficiency, but also exhibits excellent adaptability to operating conditions and anti-interference capabilities. Experimental results fully demonstrate that the catalyst of this invention can flexibly cope with complex and ever-changing practical application scenarios, possessing extremely high engineering application value and broad prospects for promotion in new energy and environmental protection fields such as photothermal catalytic hydrogenation of carbon dioxide (CO2) to produce high-value-added chemicals.

[0052] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, characterized in that, Includes the following steps: S1. Preparation of modified mineralized geopolymer: By mass, 12-16 parts of modified cenosphere powder and 5-12 parts of alkaline activator solution are mixed and stirred, and cured in a CO2 atmosphere at 50-70℃ for 24-48 hours. After demolding, the mixture is crushed and ground through a 200-300 mesh sieve to obtain the modified mineralized geopolymer. S2. Composite and cross-linking reaction: Mix 14-18 parts of modified mineralized geopolymer with 80-150 parts of deionized water to form a uniform slurry, add 1.5-4 parts of silane coupling agent to modify porous cobalt oxide, ultrasonically disperse for 10-20 min, and then mechanically stir at 40-60℃ for 2-4 h to obtain geopolymer / porous cobalt oxide composite slurry; S3. Drying and heat treatment: Dry the geopolymer / porous cobalt oxide composite slurry at 40-80℃ for 24-48h, wash it with water 3-5 times, dry it again at 40-80℃ for 24-48h, and then heat treat it in air at 350-450℃ for 20-40min to obtain the intermediate catalyst. S4, Silver doping: Add 15-20 parts of intermediate catalyst and 0.15-0.4 parts of soluble silver salt to 150-300 parts of deionized water. After ultrasonic dispersion, add 30-100 parts of sodium borohydride alkaline solution dropwise and stir for 0.5-1 hour. Wash with distilled water and anhydrous ethanol alternately 3-5 times, dry in a vacuum drying oven at 50-70℃ for 3-5 hours, and then pass through a 300-500 mesh sieve to obtain a geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst. The preparation of the modified celery micropowder includes the following steps: S11. Weigh 180-500 parts of anhydrous zinc chloride solid by mass, and slowly add it to 120-300 parts of deionized water under stirring and heating at 60-80℃. After the solid is completely dissolved and cooled to room temperature, adjust the solution density to 1.65-1.75 g / cm³ to obtain the initial heavy liquid. S12. Mix 100-200 parts of fly ash with the initial heavy liquid at a liquid-solid mass ratio of 3:1-5:1, stir and disperse at 60-80℃, then separate by hydrocyclone separator or static sedimentation, and collect the floating low-density cenosphere phase. S13. Mix the floating low-density cenosphere phase with 300-800 parts of deionized water, and perform hydrothermal activation treatment at 120-130℃ for 2-3 hours. After the reaction is completed, cool naturally, perform solid-liquid separation to collect the solid, and wash it with deionized water by centrifugation 3-4 times. Then dry it at 105-110℃, grind it through a 200-300 mesh sieve to obtain modified cenosphere micro powder. The preparation of the silane coupling agent modified porous cobalt oxide includes the following steps: S21. By mass, add 15-30 parts of porous cobalt oxide to 150-300 parts of ethanol-water mixed solution, adjust the pH to 3-4 with glacial acetic acid, add 0.15-1.5 parts of silane coupling agent KH-560, ultrasonically disperse at 40-60℃ for 2-4 hours, and then stir and reflux at 60-80℃ for 4-6 hours. S22. After the reaction is complete, the solid is collected by centrifugation, washed 3-5 times with anhydrous ethanol, dried under vacuum at 80-100℃ for 10-14h, and ground through an 800-1200 mesh sieve to obtain silane coupling agent modified porous cobalt oxide. The preparation of the porous cobalt oxide includes the following steps: S211. By weight, dissolve 80-120 parts of water-soluble cobalt salt in 400-1000 parts of deionized water, add 40-100 parts of precipitant, and stir at 60-80℃ until completely dissolved. S212 is then transferred to a polytetrafluoroethylene reactor and hydrothermally reacted at 120-160℃ for 12-24 hours to generate a porous cobalt hydroxide precursor. S213. After the reaction is complete, centrifuge and wash until neutral, dry at 80-100℃, then calcine in air at 300-400℃ for 2-3 hours, grind through an 800-1200 mesh sieve to obtain porous cobalt oxide.

2. The method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst according to claim 1, characterized in that, The alkaline activator is prepared by mixing sodium hydroxide, anhydrous sodium metasilicate and water in a mass ratio of 1:(2-4):(5-10) and then allowing it to stand and age for 12-24 hours. The soluble silver salt is one or more of silver nitrate, silver acetate, silver perchlorate, or silver trifluoromethanesulfonate.

3. The method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst according to claim 1, characterized in that, The ethanol-water mixture contains 90%-95% ethanol by mass.

4. The method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst according to claim 1, characterized in that, The water-soluble cobalt salt is one or more of cobalt nitrate hexahydrate, cobalt chloride, cobalt acetate, or cobalt sulfate; The precipitant is one or more of urea, hexamethylenetetramine, or ammonium carbonate.

5. The method for preparing a geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst according to claim 1, characterized in that, The concentration of the sodium borohydride alkaline solution is 0.1-0.5 mol / L.

6. A geopolymer / cobalt oxide / silver-doped adsorption-photothermal catalyst, characterized in that, The geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst is prepared by the preparation method described in any one of claims 1-5.

7. The application of the geopolymer / cobalt oxide / silver doped adsorption-photothermal catalyst as described in claim 6 in the photothermal catalytic carbon dioxide hydrogenation reaction.

Citation Information

Patent Citations

  • Method for preparing geopolymer photocatalyst from municipal solid waste incineration fly ash

    CN111569917A

  • Fenton-like catalyst as well as preparation method and application thereof

    CN115814796A